Die NG Kerk se identiteitskrisis Deel 2: Huidige bewegings, tendense of mutasies - Steyn, GJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The Identity Crisis of the Dutch Reformed Church Part 2:Current Movements, Trends, or Mutations There are at least five big movements to be identified within the Dutch Reformed Church. They are traditional(ist), charismatic, rationalist, mystic and syncretistic movements. However, the situation is more complex as there are also hybrids between different movements. The characteristics of these “big five” are nonetheless discussed. The contribution concludes with some guidelines and challenges for a way forward.